The role of Facebook in developing digital citizenship skills among a sample of Tishreen University students (sociological study) - صبح غيداء; يسرى زريقة (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The aim of this research is to determine the role of Facebook in developing digital citizenship skills among a sample of Tishreen University students, and the impact of the variables (gender, place of residence, college) on that. In order to achieve the objectives of the research, the descriptive approach was used by designing a questionnaire consisting of (24) statements. It was distributed to the research sample, which consisted of (654) male and female students from a number of faculties at Tishreen University, and the most important results of the research were: - The role of Facebook in developing digital citizenship skills among the research sample of Tishreen University students came according to the following order: (digital security, digital behavior, digital access) with a high degree, and digital safety and digital culture with a medium degree. - There are statistically significant differences in the role of Facebook in developing digital citizenship skills among the research sample individuals according to the gender variable in favor of females. - There are no statistically significant differences in the role of Facebook in developing digital citizenship skills among the research sample individuals according to the place of residence variable. - There are no statistically significant differences in the role of Facebook in developing digital citizenship skills among the research sample individuals according to the college variable.